Hybrid retinoid analogs as instruments for the nanobiophotonic researches - A. A. Khodonov; A. V. Laptev; A. Yu. Lukin; N. E. Belikov; M. A. Fomin; O. V. Demina; D. A. Skladnev; S. A. Tyurin; V. I. Shvets (Тонкие химические технологии)
This mini-review presents experimental data obtained by the authors in the context of a cycle of structural-functional research on bionanophotochrome bacteriorhodopsin carried out during the past 10 years. We reviewed the synthetic routes and structure-spectral parameters-properties relationship for a number of series of hybrid retinoid analogs and bacteriorhodopsin analogs based on them.